Planning the flight routes of the unmanned aerial vehicle by solving the travelling salesman problem - Vorotnikov, Vladimir; Gumenyuk, Igor; Pozdniakov, Pavel (Technology audit and production reserves, 2017)
The methods for solving the traveling salesman problem: Monte Carlo, reduction of rows and columns, averaged coefficients for planning the flight paths of unmanned aerial vehicles, and the results of the work are analyzed. The solution of the traveling salesman problem allows to reduce the time for decision making and UAV costs when planning flights. It is established that the first two solve the problem with some errors, and, when using the Monte Carlo method, these errors tend to increase, and the method of reduction of rows and columns minimizes. When using the method of averaged coefficients, the traveling salesman problem is solved more optimally in comparison with the methods considered by the distance and time criterion for solving the problem. This method gives a significant gain (5–10 %) for these criteria. The relevance and importance of the application of this method is in civil or military operations using UAVs in the face of limited decision-making time in the planning and energy resources of the aircraft.